Dermatoscopic aspects of the Microphthalmia with Linear Skin Defects (MLS) Syndrome - Hiram Larangeira de Almeida Jr; Gabriela Rossi; Luciana Boff de Abreu; Cristina Bergamaschi; Alessandra Banaszeski da Silva; Kerstin Kutsche (Sociedade Brasileira de Dermatologia, 2014)
The association of microphthalmia and linear skin defects was named microphthalmia with linear skin defects syndrome (MLS) or MIDAS syndrome (microphthalmia, dermal aplasia, and sclerocornea), an X-chromosomal disorder manifesting mainly in females. We examined a female newborn with facial linear skin defects following the Blaschko lines. Computer tomography and ophthalmological examination confirmed bilateral microphthalmia. An interstitial microdeletion at Xp22.2, encompassing the entire HCCS gene, was identified. Dermatoscopic examination showed erythematous linear areas with telangectasias and absence of sebaceous glands, which appear as brilliant white dots. Vellus hairs were also absent in the red areas. Dermatoscopy could help to establish the diagnosis of MLS/MIDAS syndrome by confirming the aplastic nature of the lesions.